If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+15+12x=78
We move all terms to the left:
-3x+15+12x-(78)=0
We add all the numbers together, and all the variables
9x-63=0
We move all terms containing x to the left, all other terms to the right
9x=63
x=63/9
x=7
| 8/5v-1/5v=-49/30 | | 3(2x+6)=15-3 | | 4-7x=2(x-7$ | | g/5+12=23 | | −3(4x+3)+4(6x+1)=4 | | (1÷3)×(y+7)=3×(y-1) | | –8g+3=–9g | | (4x+6)=44° | | 4g+2+8g=56 | | x2x+10=4x+2 | | 2x+4=3x–8 | | 0=-2t^2+48t-10 | | 0.5(20d+10)=12d-3 | | 8y+3y-y+5=45 | | 8x-17=7x-58 | | -3v+9v+1=13 | | 7x9= | | 6y-15=180 | | 18x+35=11x | | 4x+3x+5+4x+7=180 | | -2x+3=1/2(4x-10)+2 | | 32+0.1c=1 | | 4x+39.58=52.22 | | 6+10=2h | | 9x-2=(3x+4) | | 2m-7=8m+2 | | 10(3k-2)=40 | | 27^x=30 | | 2x+x+10=90+x | | 4y/2=200/2y | | 8(y+4)-2y-1)=70-3y | | -x+4(3x-4)=-40+3x |